The psychometric properties of the Bidimensional Acculturation Scale for Marriage-Based Immigrant Women in Taiwan. - Hung-Hui Chen (Public Library of Science (PLoS), 2021)
Introduction Marriage-based immigrant women are increasing around the world. Although bi-dimensional acculturation is important for immigrant women's health, the existing scales have mainly been developed for immigrant women in Western countries and hence some items may not be suitable for Asian contexts. Thus, we developed and evaluated the Bidimensional Acculturation Scale for Marriage-Based Immigrant Women (BAS-MBIW) in Taiwan. Methods The BAS-MBIW was developed based on a literature review and clinical observations. Bi-dimensional acculturation involves "adaptation to host culture (acculturation)" and "maintenance of heritage culture (enculturation)." The initial scale included two 24-item subscales. The validation samples were 310 marriage-based immigrant women who were pregnant for at least twelve weeks in Taiwan. The BAS-MBIW was assessed and modified by experts. Data analyses included factor analysis, Pearson's correlation, and Cronbach's alpha coefficient. Results Expert reviews and factor analysis indicated that the scale had acceptable content and construct validity. The validated scale includes two 19-item subscales, encompassing six domains: language, media, food preference, cultural heritage, social interaction, and shopping and merchandise preference, with good internal consistencies (Cronbach's alpha coefficient is 0.88 for acculturation and 0.83 for enculturation). Acculturation was positively related to local language ability and duration of immigration but negatively related to age at immigration, stress, and depression; whereas enculturation was positively related to age at immigration, stress, and depression but negatively related to duration of immigration, indicating convergent validity. Conclusions The BAS-MBIW offers reliable and valid assessments of pregnant immigrant women's level of acculturation and enculturation in Taiwan. The BAS-MBIW could be used to assess bi-dimensional acculturation among marriage-based immigrant women.